Relationship between plasma total homocysteine and the severity of renal function in Chinese patients with type 2 diabetes mellitus aged ≥75 years. Issue 27 (2nd July 2020) - Ma, Ning; Xu, Ning; Yin, Dong; Liu, Weiwei; Wu, Mengping; Cheng, Xingbo
Abstract : Abstract: We aimed to investigate the relationship between total homocysteine (tHcy) levels in the plasma and renal function severity in patients with type 2 diabetes mellitus (T2DM) aged ≥75 years. We included 221 patients with T2DM aged ≥60 years (59 aged ≥75 years). tHcy levels among the 4 groups of patients aged ≥60 years significantly differed, but not in those aged ≥75 years. tHcy levels in patients aged ≥60 years were negatively correlated with the estimated glomerular filtration rate. The area under the receiver operating characteristic curve of tHcy for predicting diabetic kidney disease (DKD) was 0.636. Fasting c-peptide and creatinine were independently associated with tHcy levels in patients aged ≥60 years, whereas insulin and creatinine were independently associated with tHcy levels in those aged ≥75 years. tHcy concentrations were elevated in T2DM and can potentially serve as a risk factor for DKD, but it is not an ideal biomarker.